Modified desirability function for optimization multiple responses / Nurul Awanis Abu Samah and Siti Nurliana Noraziman - Abu Samah, Nurul Awanis; Noraziman, Siti Nurliana (2018)
Harrington’s desirability function approach is usually used to overcome the problem of optimization of multiple responses simultaneously. However, this method will give a huge impact in the presence of outliers. After that, in this case, it is not reliable to use Harrington’s desirability function method to find the optimum responses because it is not resistant to outliers. Thereupon, Modified Geometric Mean (MGM) approach is proposed as an alternative to estimate the parameter as this approach is resistant to outliers. Numerical example study is carried out to compare the performance of the proposed method with existing procedures. Based on the value of the overall desirability function, D , MGM is better compared with Harrington’s desirability function as it is clearly shows that the value of D is larger and the standard error of the MGM approach is smaller. It is clearly shows that, the MGM approach can be an alternative method in dealing with the presence of outliers